Severe Degree of The Obesity Has More Comorbid Factors and more Severe of The Knee Osteoarthritis - Natalia Loekito; Tirza Z. Tamin; I Nyoman Murdana (Indonesian Journal of Physical Medicine & Rehabilitation, 2016)
Background : Obesity is a risk factor for knee osteoarthritis (OA). The major problem of OA are pain and decreased of knee muscle strength cause a decline of functional capacity, and lead to disability. Aim of this study is to describe the profile of obese patients with knee OA to prevent disability. Methods : A descriptive study was conducted from September 2016 - March 2017. Subjects were obese patients with knee OA, age ranging from 40-80 years with sedentary lifestyle, with Physical level (PAL)<1.4. Results : Most of the subjects have age>60 y.o(58.8%) anf were female (92.7%). The frequency of Obesity grade II (56.1%) and OA knee grade III (56.1%) were the most frequent. There were higher prevalence of comorbid factors on subjects with grade II of obesity i.e, hypertension, dyslipidemia, and diabetes mellitus (32 vs 27, 18 vs 5, 7 vs 2) respectively. THis study found 41 subjects has knee OA, consist grade II was 18 (43,9%), grade II was 23 (56,1%), Besides, there were higher prevalence of more severe knee OA on grade II than grade I of obesity subjects (29 vs 12).Conclusions : Higher grading of obesity has more prevalence of comorbid factors, as well as has more severe of knee OA Keyword : obesity, comorbid factors, knee osteo arthritis